LEGAL PROTECTION OF PATIENTS NEEDING EMERGENCY TREATMENT NEGLECTED BY DOCTORS IN HOSPITAL EMERGENCY UNITS - Yeni Nuraeni (Fox Justi : Jurnal Ilmu Hukum, 2023)
One of the main health-related problems is the health services provided by doctors. The services provided by these doctors are in the form of assistance or assistance based on the patient's trust in the doctor. The purpose of this research is to find out the responsibility of the home for negligence in patients who need emergency care which was neglected by a doctor resulting in the patient's death, and the implementation of the patient's rights in medical services at home in accordance with Law Number 29 of 2004 concerning Medical Practice. The method used in this study is descriptive analytical with a normative juridical approach. The Hospital Law provides legal certainty so that hospitals can carry out their management functions more optimally. If in hospital services and other medical personnel refuse to carry out treatment and do not provide treatment that is in accordance with the patient's medical needs, it is an act against the law. The actions of doctors and medical personnel that cause harm to patients, let alone until the patient dies, the hospital can be legally held accountable, so that it can be prosecuted criminally and civilly.